1990
DOI: 10.1073/pnas.87.17.6624
|View full text |Cite
|
Sign up to set email alerts
|

A tumor suppressor-dependent inhibitor of angiogenesis is immunologically and functionally indistinguishable from a fragment of thrombospondin.

Abstract: A secreted inhibitor of angiogenesis that is controlled by a tumor suppressor gene in hamster cells has been found to be similar to a fragment of the platelet and matrix protein thrombospondin. The two proteins were biochemically similar and immunologically crossreactive and could substitute for one another in two functional assays. Human thrombospondin inhibited neovascularization in vivo and endothelial cell migration in vitro, as does the hamster protein, gpl40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
583
1
15

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 944 publications
(615 citation statements)
references
References 40 publications
10
583
1
15
Order By: Relevance
“…It has been demonstrated previously that secretion of the inhibitor of angiogenesis, thrombospondin-1 (Good et al, 1990), is responsible for the inhibitory activity seen in media conditioned by early passage normal and Li Fraumeni ®broblasts and that TSP mRNA and protein levels fall dramatically upon immortalization (Dameron et al, 1994a,b). Quantitative Western analysis of media conditioned by ®broblasts at various stages of progression showed that secreted TSP protein levels were very high prior to immortalization, when it constituted up to 10% of total protein secreted by the cells (Figure 2).…”
Section: Changes In Inhibitory Tspmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated previously that secretion of the inhibitor of angiogenesis, thrombospondin-1 (Good et al, 1990), is responsible for the inhibitory activity seen in media conditioned by early passage normal and Li Fraumeni ®broblasts and that TSP mRNA and protein levels fall dramatically upon immortalization (Dameron et al, 1994a,b). Quantitative Western analysis of media conditioned by ®broblasts at various stages of progression showed that secreted TSP protein levels were very high prior to immortalization, when it constituted up to 10% of total protein secreted by the cells (Figure 2).…”
Section: Changes In Inhibitory Tspmentioning
confidence: 99%
“…The membrane was blocked overnight with 7% Blotto (Carnation non-fat dried milk in incomplete PBS) and probed with anti-thrombospondin monoclonal antibodies A4.1 (Good et al, 1990). After incubation for 2 h at room temperature the membrane was washed and secondary anti-mouse HRP-conjugated antibody (Sigma Corp, St Louis, MO) was added in 1% blotto.…”
Section: Western Analysismentioning
confidence: 99%
“…Reexpression of THBS1 reduced tumor growth, angiogenesis and metastasis in a hemangioma cell line (Sheibani and Frazier, 1995) and a breast cancer cell line (WeinstatSaslow et al, 1994). In addition, several tumorsuppressor genes appear to regulate angiogenesis through THBS1 expression (Hsu et al, 1996;Dameron et al, 1994;Good et al, 1990). However, no mutations, translocations or deletions involving THBS1 have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Several angiogenic factors participated in HCC progression, including vascular endothelial growth factor (VEGF), [1][2][3] transformation growth factor-a (TGF-a), 4 insulin-like growth factor (IGF-II), 5 and hepatocyte growth factor. 6 However, liver is also a rich source for the precursors of many endogenous angiogenesis inhibitors such as thrombospondin, 7 angiostatin, 8 and endostatin. 9 Among these inhibitors, endostatin, a 20-kDa protein derived from carboxy (C)-terminal proteolytic fragment of collagen XVIII (C18), has attracted tremendous attention since its discovery because of its potency to inhibit neovascularization and tumor growth without inducing drug resistance in mice.…”
mentioning
confidence: 99%